Communication—Lithium Difluorophosphate as an Electrolyte Additive to Improve the High Voltage Performance of LiNi0.5Co0.2Mn0.3O2/Graphite Cell. Issue 2 (31st January 2018) - Hong, Shu; Hong, Bo; Song, Wenfeng; Qin, Zhaoming; Duan, Boyu; Lai, Yanqing; Jiang, Feng
Abstract : Lithium difluorophosphate (LiDFP) is used as an electrolyte additive to improve the electrochemical performances of LiNi0.5 Co0.2 Mn0.3 O2 (NCM523)/graphite cells operating at a high charging cutoff voltage. LiDFP additive generates a more uniform, extremely stable, and lower resistance passivation film on the cathode surface. This passivation film not only suppresses the subsequent decomposition of electrolyte, but also prevents the dissolution of transition metal ions from NCM523 particles, resulting in improved cyclic stability and discharge capability of NCM523/graphite cells. With electrolyte contained 1.0 wt% LiDFP, the 18650 batteries achieves a capacity retention of 88.2% after 300 cycles at 3.0∼4.4 V and 90.0% after 200 cycles at 3.0∼4.45 V, comparing to 77.9% and 66.3% of the batteries without additive.